3D Printing in Space. (November 2014) - Leach, Neil
<x xml:space="preserve">Abstract</x> The cost of transporting raw materials into Space is prohibitive ‐ potentially US$2 million for a single brick to be shipped to the Moon. This means that the future of extraterrestrial construction rests on the development of technologies that are able to employ in‐situ materials, such as lunar dust. Guest‐Editor Neil Leach is a NASA Innovative Advanced Concepts Fellow, collaborating with colleagues from the University of Southern California (USC) on a research project developing a robotic fabrication technology capable of printing structures on the Moon and Mars. Here he describes the inroads that NASA and European Space Agency (ESA) consortia are independently making into 3D‐printed fabrication technologies.